The Australian fish chorus catalogue (2005–2023) - Hawkins, Lauren Amy; Erbe, Christine; Becker, Alistair; Browne, Ciara E.; McCordic, Jessica; McWiliam, Jamie; Parnum, Iain M.; Parsons, Miles James; Rivero, Natalie; Ward, Rhianne; White-Kiely, Dylan; McCauley, Robert D. (Frontiers in Remote Sensing, 2024)
Biological sources are significant contributors to aquatic soundscapes. Soniferous fish can dominate the soundscape in certain locations, at specific times and frequencies, particularly during the production of choruses. Passive acoustic monitoring of fish choruses can provide important ecological information about soniferous fish populations. This study presents the Australian Fish Chorus Catalogue, an inventory of fish choruses detected from 83 locations in Australian estuarine and marine waters. The Australian Fish Chorus Catalogue contains data on fish chorus occurrence and the spectral and temporal measurements, spectrographic images, and audio examples of 301 fish choruses. This catalogue has been developed to establish the foundations of an ongoing effort to document, quantify, compare, and track Australian fish choruses. We hope this open-access data depository will be used as a reference for future research and will facilitate an increase in understanding of fish choruses, which can then be applied to the monitoring and management of fish populations and their respective ecosystems.